An Inductive Construction of Rigid Panel-Hinge Graphs and Their Applications to Form Design. (March 2015) - Kobayashi, Yuki; Katoh, Naoki; Okano, Tomohiro; Takizawa, Atsushi
A panel-hinge framework is a structure composed of rigid panels connected by hinges. It was recently proved that at a generic position, the rigidity of panel-hinge frameworks can be predicted by examining a certain combinatorial property of the underlying graph. In this study, we apply such combinatorial characteristics to create design forms. When considering the application of design forms, we must also take into account non-generic cases. In this paper we develop two new approaches; the first one that the method inductively generates non-generic rigid panel-hinge frameworks consisting of orthogonal panels and the second one that inductively generates non-generic rigid panel-hinge frameworks based on fractal geometry coupled with space-filling convex polyhedron as a construction unit. We will give examples of forms created by the proposed method in order to demonstrate the applicability of the proposed methods to design forms.